Mass Productlon of Field Planting Stock of Dendrocalamus hamiltonii Vegetatively through Macro-proliferation - Kumar, Adarsh; Pal, Mohinder; Kumar, Shiv (Indian Forester, 1992)
A technology developed for production of field planting stock of Dendrocalamus hamiltonii has been described. The advantage of this technology is that it is low cost, simple, easy and involves the use of locally available materials and has direct application in the field. The dependence on bamboo seed production in nature is totally eliminated from second year onwards for mass production of field plantable bamboo saplings. The planting stock, developed vegetatively through macro-proliferation remain small in size which is additional advantage as these are easy to handle and transport. The technology developed, will help to overcome the scarcity of planting stock of bamboo in absence of seed. A plan has been developed and described in this paper for production of 16,000 field plantable saplings of D. hamiltonii vegetatively every year for any desired number of years. Depending upon the targets and the facilities available, the planting stocks in multiples of 16,000 can be produced each year.